Four Generations of ECMWF Reanalyses: An Overview of the Successes in Modeling Precipitation and Remaining Challenges for Freshwater Budget of Ocean Models - Raphael Dussin (Earth and Space Science)
Abstract This study reviews the progress made in modeling precipitations in four generations of reanalyses from the European Center for Medium‐Range Weather Forecasts, using traditional metrics and a new set of regional metrics. Regional metrics at oceanic basin scales and large land catchment areas over the continents allow for a more comprehensive analysis of the performance of the reanalyses. This leads to the conclusion that significant progress has been made in the past several decades in both the atmospheric model and the assimilation system at the ECMWF, leading to more realistic precipitation. The most recent ERA5 reanalysis outperforms ERA‐Interim and its predecessors by all metrics considered. ERA5 is then used to force a modern ocean general circulation model, and the results show an improvement in terms of the freshwater budget, particularly after the year 2000. However, uncertainties remain about the magnitude and trends of the modeled evaporation.